Urbanization, economic growth and environmental pollution: Evidence from China - Liang, Wei; Yang, Ming (Sustainable computing informatics and systems, 2019)
•The interaction between urbanization, economic growth, and environmental pollution in three directions is investigated.•A model of “urbanization-economic growth” and a “simultaneous equation model” are constructed.•There is an environmental Kuznets inverted U curve between economic growth and environmental pollution. As the state is vigorously promoting the construction of new urbanization in China, it is of great practical significance to study the interaction between urbanization, economic growth, and environmental pollution in three directions for the scientific planning of urbanization. Based on panel data of 30 provinces and cities in China during 2006–2015, we built the “Urbanization economic growth model” and a “simultaneous equation model.” The results show that urbanization promotes economic growth through the accumulation of physical capital, knowledge capital, and human capital; that the relationship between economic growth and urbanization is a benign interaction; that environmental pollution has a significant inhibitory effect on urbanization; and that there is an environmental Kuznets inverted U curve between economic growth and environmental pollution, and between urbanization and environmental pollution. On this basis, this paper puts forward some policy suggestions on how to enhance the positive interaction between urbanization and economic growth and promote the construction of new green urbanization.